Research Progress and Prospect Analysis of the Application of Flax Lignans - Li, Yazhi; Zhao, Xinlin; Wang, Yufu; Qiu, Caisheng (Journal of natural fibers, 2024)
Lignan is one of the important components in flaxseed and has been paid increasing attention owing to its special therapeutic effects on many diseases. Herein, we retrieved the recently published studies on flaxseed lignan through the Web of Science to give a comprehensive understanding of the research advances of flaxseed lignan. Results showed that flaxseed lignan has been extensively applied to many industries, such as food, medicine, and cosmetics. Flaxseed lignan has great potential in the pharmaceuticals industry, many studies have proven its performance on antioxidant, anti-tumor, anti-cardiovascular disease, prevention of osteoporosis and diabetes. However, the depths of the research need to be enhanced and the mechanisms of lignan in curing each disease should be further clarified. Flaxseed lignan presents good performance in anti-skin sagging, maintains skin elasticity and radiance, and significantly delays the aging process. In addition, flaxseed lignan has been used in functional foods and dietary supplements in the food industry. Therefore, as a multiuse material, flaxseed lignan will play important roles in the product and development and utilization of food, medicine, and cosmetic and, accordingly, its source plant--flax, will also receive more attention in the future.